(untitled) (Practitioner Research, 2023)
In this millennium era, the English language proficiency of tourism entrepreneurs must be looked into and improved. This is due to the tourism industry’s tremendous growth that requires mastery of the English language, as English is now widely acknowledged as the worldwide language of communication. In addition, due to the scope of their work that needs to interact with international tourists, it is essential for them to be able to communicate in the English Language. This study aims to discover the challenges faced by them and their way of having to learn, master the English language and overcome these challenges. This study will follow a qualitative approach where the researchers engaged in semi-structured interviews as preliminary data, interviewing two tourism entrepreneurs located in various parts of the tourist island of Langkawi. Thematic analysis was employed to interpret the collected data and generate appropriate themes and sub-themes for the study. The findings illustrated that tourism entrepreneurs operating on Langkawi Island encountered various obstacles with their English-speaking skills. These challenges included difficulties in understanding unfamiliar accents and the necessity for additional resources to effectively communicate with international tourists. The entrepreneurs expressed their desire for support in enhancing their English language proficiency. The data also revealed that these individuals overcame their difficulties by actively engaging in regular interactions with international tourists and making use of mobile applications to improve their ability to speak English.